National Trends in Pediatric Facial Fractures: The Impact of Health Care Policy. Issue 2 (24th November 2020) - Jenny, Hillary E.; Yesantharao, Pooja; Redett, Richard J.; Yang, Robin
Abstract : Background: Traumatic injuries are significant sources of morbidity and mortality in the pediatric population. Using a national database, this study aims to characterize pediatric facial fracture management and the effect of health care policy changes on populations receiving treatment. Methods: A retrospective cohort study was performed using Healthcare Cost and Utilization Project Kids' Inpatient Database databases from 2000 to 2016. Pediatric patients admitted with a facial fracture diagnosis were included. Clinical outcomes include mortality, reduction of fracture during hospital stay, and open fracture reduction. The impact of the Affordable Care Act on patient demographics and management was assessed. Results: Between 2000 and 2016, 82, 414 patients were managed for facial fractures, 8.3 percent of whom were managed after implementation of the Affordable Care Act ( n = 6841). Mean age was 15.2 years, and the male-to-female ratio was 2.9:1. Significant racial disparities were identified before the Affordable Care Act: African American and Native American patients had decreased odds of having facial fracture reduction during the initial hospital stay (OR, 0.84 and 0.86, respectively), and identifying as either Hispanic or Native American was associated with higher odds of mortality (OR, 1.4 or 2.4, respectively). Race was not contributory to patient mortality after the Affordable Care Act. Before Affordable Care Act implementation, patients receiving care with no charge (including charity care/charity research) had lower odds of having an open reduction or any reduction; insurance status was not contributory to management after the Affordable Care Act. Conclusion: Although the Affordable Care Act may have increased access to care for certain populations, race- and sex-associated differences in mortality rate and fracture management should be further investigated to ensure a national standard of equitable patient care.